Acute Pathophysiological Effects of Intratracheal Instillation of Budesonide and Exogenous Surfactant in a Neonatal Surfactant-depleted Piglet Model - Chia-Feng Yang; Mei-Jy Jeng; Wen-Jue Soong; Yu-Sheng Lee; Pen-Chen Tsao; Ren-Bin Tang (Elsevier, 2010)
Chronic lung disease continues to be a major complication in premature infants with severe respiratory distress syndrome (RDS). This is despite having advanced ventilatory care, prenatal corticosteroids, and postnatal surfactant therapies. The combined use of intratracheal corticosteroids and surfactant may not only recruit the lungs, but also alleviate pulmonary inflammation in severe RDS. Methods: Fifteen newborn piglets received repeated pulmonary saline lavage to induce surfactant-depleted lungs, mimicking neonatal RDS. They were randomly divided into three groups: control group receiving no treatment; surfactant (Surf) group, treated with standard intratracheally instilled surfactant (100 mg/kg); and Budesonide plus surfactant (Bude + Surf) group, treated with intratracheally administered mixed suspension of budesonide (0.5 mg/kg) and surfactant (100 mg/kg). Blood samples were taken every 30 minutes for 4 hours. Lung tissue was examined after the experiment. Results: Significantly better oxygenation with higher PaO2 and alveolar-arterial oxygen difference was noted in the Surf and Bude + Surf groups, compared with the control group (p < 0.05), but there were no significant differences between the Surf and Bude + Surf groups. Pulmonary histologic damage was also markedly alleviated in both the Surf and Bude + Surf groups, compared with the control group, and lung injury scores were significantly decreased in the Surf and Bude + Surf groups, compared with the control group (p < 0.05). Conclusions: Intratracheal instillation of surfactant or surfactant plus budesonide can improve oxygenation and pulmonary histologic outcome in neonatal surfactant-depleted lungs. The additional use of budesonide does not disturb the function of the exogenous surfactant. Intratracheal administration of a corticosteroid combined with surfactant may be an effective method for alleviating local pulmonary inflammation in severe RDS.